Edukasi Pencegahan Low Back Pain Pada Nelayan Desa Kampung Beru, Kabupaten Takalar - Rahmadani, Yulianah; Dwiseli, Firmita (-, 2025)
Based on the International Labour Organization (ILO) 2018, more than 1.8 million work-related deaths occur every year in the Asia and Pacific region, and even two-thirds of the world's work-related deaths occur in Asia. According to the Directorate General of Health Services of the Ministry of Health of the Republic of Indonesia (Minsitry of Health, RI), Low Back Pain (LBP) in Indonesia is 18%. The incidence rate in Indonesia based on patient visits from several hospitals is around 3-17% of Low Back Pain complaints. The method used is a lecture, which explains to community groups through PowerPoint presentations related to low back pain prevention material, followed by questions and answers, providing opportunities for the community to ask questions related to the material presented. After the implementation of community service in the form of counselling activities to prevent Low Back Pain for fishermen in Kampung Beru, Takalar Regency, it is hoped that there will be attention from all elements, especially the Takalar Regency government, to facilitate the community, especially those who work as fishermen, to practice safe and safe ways of working to prevent LBP.